1993
DOI: 10.1111/j.1651-2227.1993.tb12791.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal bacterial septicemia in a tropical area. Four-year experience in Guadeloupe (French West Indies)

Abstract: During a four-year study (1 987-1990) at the Neonatal Department, University Hospital Pointe-a-Pitre (French West Indies), blood culture was systematically performed on all admitted newborns. The incidence of septicemia was 48 of 1000 admissions and 8.9 of 1000 inborn live births. Among the 107 neonatal positive blood cultures, group B streptococcus accounted for 37% of blood culture isolates and was the most frequent cause of septicemia. The overall mortality rate was 8.4%. The incidence of neonatal bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
11
2
Order By: Relevance
“…Although some other studies found that Gram positive bacteria were the commonest cause of neonatal sepsis 7,26,27 , while one study showed that the frequency of isolation of both Gram positive and Gram negatives was equal 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although some other studies found that Gram positive bacteria were the commonest cause of neonatal sepsis 7,26,27 , while one study showed that the frequency of isolation of both Gram positive and Gram negatives was equal 22 .…”
Section: Discussionmentioning
confidence: 99%
“…3 In developing countries, the incidence of neonatal sepsis ranges from 7.8 to 21.8/1000 live births, with case fatality rates as high as 38%. [4][5][6] To prevent this high mortality, appropriate preventive and therapeutic interventions must be directed against specific pathogens. However, contradictory studies and lack of etiological data from rural areas have stymied progress.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, many of these studies were hospital-based in large urban centers, with a high likelihood for inclusion of nosocomial infections and reflecting an urban population rather than the rural environment where the majority of neonatal deaths occur. Although group B Streptococcus has been a common cause of neonatal sepsis in industrialized countries, 18 its role in developing countries is less certain.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of neonatal sepsis varies from 7.1 4 to 38 5 per 1000 live births in Asia, from 6.5 6 to 8.9 7 per 1000 live births in Africa, and from 3.5 8 to 8.9 9 per 1000 live births in South America and the Caribbean. By comparison, rates reported in the United States and Australasia range from 1.5 to 3.5 per 1000 for early onset sepsis and up to 6 per 1000 live births for let onset sepsis, a total of 6-9 per 1000 for neonatal sepsis.…”
mentioning
confidence: 99%